Productive Wakaf as A Vessel for Islamic Philanthropy From the Perspective of Imam Mazhab - Fahmi Makraja; Khadijatul Musanna; Farhanah Mazalan (Journal of Management and Islamic Finance, 2026)
Previous research in the field of Islamic philanthropy primarily examined waqf through the lens of operational performance and management strategies; however, this study addressed a significant gap by comprehensively analyzing the legal status and perspectives of various Islamic schools of thought (madhhabs) regarding productive waqf. The study aimed to determine the perspectives of Contemporary Fiqh scholars regarding the legal status of productive waqf transactions. Productive waqf was identified as a vessel for Islamic philanthropy that sought to realize community welfare by channeling liquid assets to rebuild assets or provide venture capital. A qualitative research method was employed, utilizing a library research approach that gathered data from classical and contemporary texts containing the opinions of the Shafi'i, Hanafi, and Imam al-Zuhri scholars. The results indicated that the scholars of the Shafi'i and Hanafi schools, along with Imam al-Zuhri, viewed productive waqf transactions as permissible, as historical precedents for waqf in the form of dinars and dirhams existed since their eras. In the Indonesian context, this permissibility was further strengthened by the approval of the DSN-MUI and the enactment of Law No. 41 of 2004 concerning waqf.